Sustentabilidade e controladoria: um estudo em uma empresa de varejo de moda e eletroeletrônicos - Lima, Eriko Kimura (2014)
The main objective of this study was to investigate the perception and contribution of the managers of Controller s Department to sustainability in a retail, fashion and consumer electronics industry. The research fits into the business environment in which sustainability is increasingly present in the strategic agenda of corporate executives due to greater stakeholder engagement regarding socially responsible organizations attitude as a theme. In this intent, we posed the following research question: how is the adoption of sustainability based on the triple bottom line model influencing the practices of the Controller s Department of the company? Thus, for conducting this research, it has been assumed that the economic view is the prevailing one in the functions of the Controller s Department and managers are still unclear about the contribution of the management in the social and environmental aspects. Therefore, to achieve the research objectives, we proceeded with analysis of the literature on the topic of sustainability and Controllership. The typology of this research is exploratory with qualitative approach because it aimed to investigate how sustainability is influencing the Controller s Department and the contribution of managers by adopting the theme. The method used was case study. The sample was selected by the criterion of accessibility and processing of data was done through content analysis. The research findings indicate that sustainability issue still needs further understanding of the managers of Controller s Department in their conceptual, procedural and organizational aspects; which is the economic view that prevails in the functions and activities of managers.